Production process of di-amyl ether and its use as an additive in the formulation of aviation fuels. (15th September 2018) - Cataluña, Renato; Shah, Zeban; Venturi, Vanessa; Caetano, Nattan R.; da Silva, Bibiana Porto; Azevedo, Carla M.N.; da Silva, Rosângela; Suarez, Paulo A.Z.; Oliveira, Lincoln P.
Abstract: This work deals with the production of a high added value ether used as additive in aviation fuel. The ether was synthesized from the iso -amylenes present in the C5, the five-carbon isomer cuts in petroleum distillates and the iso -amyl alcohol found in the fusel oil of the alcohol industry. Qualitative analyses like mass spectrometry and nuclear proton magnetic resonance spectroscopy confirmed the formation and structure of the proposed semi-renewable ether, the high molecular weight di-amyl ether (DAE). Optimization of the reaction parameters resulted in a conversion of the 48%, molar fraction, iso -amylenes when using an adiabatic profile reactor. By using this ether production and purification process, the final product showed 98% w/w of purity. The synthesized di-amyl ether presented physicochemical properties similar to the commercial aviation kerosene. The physicochemical properties evaluation performed in the mixtures of di-amyl ether in aviation kerosene showed relevant improvements, such as reduction of the freezing point and increase of the oxidation reaction rate. The results showed this novel fuel has great potential to be used in gas propulsion turbines in commercial flights and is also strategic for military aircraft.